Modelling glacier-bed overdeepenings as sites for possible future lakes in deglaciating landscapes of the French Alps - Cathala, Maëva; Magnin, Florence; Linsbauer, Andreas; Haeberli, Wilfried (Géomorphologie : relief, processus, environnement, 2021)
International audience Glacier retreat results in major landscape changes including the formation of new lakes in Glacier-Bed Overdeepenings (GBOs) that can provoke catastrophic Glacial Lake Outburst Flood (GLOF) hazards, but could also provide economic opportunities. This study aims to identify and characterize the location of potential GBOs in the French Alps as possible sites for future lakes. We first ran GlabTop (Glacier-bed Topography) and GlabTop2 models, two GIS schemes calculating glacier ice thickness and mapping potential GBOs. Their level of confidence is estimated using morphological analysis based on slope angle, crevasse fields and lateral narrowing at bedrock thresholds. 139 GBOs (>0.01km²) were predicted among which 59 have medium to very high confidence. 20 lakes are already forming at the snout of retreating glaciers, including four lakes at predicted GBOs <0,01km². The Vanoise massif hosts 43% of the predicted GBOs but the Mont Blanc massif gathers larger, deeper and more voluminous ones. Most of the predicted GBOs are below 3,500m a.s.l. as related to the elevation of the corresponding glaciers. In the Vanoise massif, many predicted GBOs have rather low confidence because of the extent of ice-cap like glaciers for which the shear stress approach used by GlabTop becomes questionable. Furthermore, 58 potential GBOs were detected by visual analysis of glacier morphologies. The study highlights the relevance of combining various methods to determine GBOs and is a first step towards the anticipation of future risks and opportunities related to the formation of new lakes in the French Alps. Dans le contexte actuel de retrait glaciaire, de nouveaux lacs se forment parfois dans les surcreusements des lits glaciaires. Ces lacs peuvent provoquer ou amplifier des aléas naturels (e.g., vidange brutale d’un lac) ou être source d’opportunités économiques. Cette étude vise à identifier et caractériser les surcreusements glaciaires pour déterminer les futurs lacs potentiels dans les Alpes ...